DESIGN CRITERIA FOR MINIMUM WEIGHT OF SIMPLY SUPPORTED PLATE GIRDERS IN FLEXURE (Journal of Engineering, 2003)
This studies concerned with the optimum weight design of steel plate girders which have been used in long spans and heavy loads constructions. AISC-1989 Specification was used for design calculations, A computer program was prepared to achieve the optimum design. Flexure ard derlection were considered. The correlation between the clear depth (h) and the weight per unit length of the girder were established for different loads, spans, steel grades, minimum theoretical web thickness, and minimum practical web thickness. It was found that the optimum weight s obtained when the flange width is nearly equal to the clear distance (h) between the flanges. Also it was found that small difference in opumum weight is obtained when using the minimum theoretical web thickness and the minimum practical web thickness. It is also found that the steel grace variation results in minor effects on the optimum weight.